Tuning the sorption properties via activation treatments of a metastable Zn-1, 3, 5-benzenetricarboxylate framework with dodecahedral and cubic cages. Issue 5 (16th December 2014) - Ma, Huanqing; Wang, Shujun; Liu, Hongyan; Meng, Fanbin; Zheng, Wangang; Gao, Weiying
Abstract : Presented here is a metastable MOF built from the alternating connection of dodecahedral and cubic cages. Three different activation treatments, vacuum-drying, freeze-benzene drying and SCD activation, were performed to optimize the porosity and gas uptakes of the metastable MOF. Abstract : Presented here is a metastable metal–organic framework built from the alternating connection of dodecahedral and cubic cages. To enhance its sorption properties, three kinds of different activation treatments were performed to decrease the deleterious effect of solvent surface tension during activation processes.